Transformation of Ukrainian Consumer Basket in Conditions of COVID-19 Pandemic - Шумей, А. (Київський національний університет імені Тараса Шевченка, 2022)
Consumer behavior and the basket of Ukrainians have undergone certain transformations due to the spread of COVID-19 and the introduction of quarantine measures. Fear, panic, uncertainty about the future, reduced income and temporary job losses were the main factors that affected consumers. First of all, this was reflected in the dynamics of changes in the structure of economic expenditures in the first half of 2020 compared to 2019. The introduction of quarantine had the features of increasing online orders, non-cash payments, purchase of long-term storage goods, medicines, and goods for the organization of work in a remote format. The increase in spending on these items has created delayed demand from consumers. The purchase of clothes, shoes and travel arrangements have been put on hold. It should be noted that such transformations were temporary. After the restrictions were lifted, people returned to their old eating habits. Research has shown that people are sensitive to information. This was reflected in the increase in the share of non-cash payments, because the mass media recommended avoiding cash payments. This experience has shown us the reasons why sellers and manufacturers must constantly monitor information and news and be able to predict further developments. Consumers must be open to working with sellers and producers so that sellers and producers can understand the consumers’ interests and meet their demands. Recommendations were developed for public authorities to improve the adaptation of public policy to changes in consumer behavior in the context of the introduction of restrictive measures for buyers in the form of quarantine; for enterprises to increase the effectiveness of enterprise policy in a pandemic; for consumers to build relationships with sellers and manufacturers on an ongoing basis.

Досліджено етапи та структура трансформації споживчого кошика в умовах поширення пандемії COVID-19. Проаналізовано динаміку зміни частки розрахунків у безготівковій формі до, під час та після запровадження карантину. Розглянуто структуру зміни витрат на продовольчі та непродовольчі товари за категоріями домашніх господарств у 2019–2021 рр. та на основі отриманих результатів виокремлено причини таких змін. Розроблено рекомендації для державних органів влади щодо покращення напрямів адаптації державної політики до зміни споживчої поведінки в умовах запровадження обмежувальних заходів для покупців у вигляді карантину; для підприємств щодо підвищення ефективності політики підприємства в умовах пандемії; для споживачів щодо побудови взаємовідносин із продавцями та виробниками на постійній основі.
Трансформація споживчого кошика українця в умовах пандемії COVID-19
Keywords: споживчий кошик; COVID-19; витрати домашніх господарств; consumer basket; household expenditures